ACCOMPLISHING HUMAN RIGHTS JUSTICE IN THE CONTEXT OF ASSETS CONFISCATION: AN EVALUATION OF THE UNITED KINGDOM DRUG LAWS ENFORCEMENT - KINGSTON, Kato Gogo (Journal of Advanced Research in Law and Economics; Vol 2 No 1 (2011): JARLE Volume 1 Issue 1(3) Summer 2011, 2017)
It is estimated that crude oil, tourism and illicit drug trade are among the top five most financially inducing business in the world. Drug cartels conducts sophisticated and well organised activities including money laundering and monitoring of large networks of their couriers. In past the decade, the United Kingdom has incurred large expenditure on the treatment of drug related illnesses and, on the enforcement of drug control laws. Several drug laws are enacted to dealing with the waves of illicit drugs in the country. There is controversy over the ways by which the properties of the drug traffickers and suspected drug dealer, are seized by the State; in order to seize anyone’s private property prior to commencement of legal proceedings to effect permanent forfeiture, the law enforcement agencies are only required to show ‘probable cause’ that the property being seized is acquired with the profit of drug crime alternatively, that the property facilitates drug criminal activities. Using data from academic materials and United Kingdom case laws, the paper argues that the United Kingdom drug trafficking laws particularly the enforcement of ‘civil asset recovery’ under the Proceeds of Crime Act 2002 and, the ‘Criminal confiscation’ under the Drug trafficking Act 1994 violates the International Human Rights Laws.
Keywords: drugs, Human Rights, UK laws, criminal property